Solution Self-Assemblies of Sequence-Defined Ionic Peptoid Block Copolymers - Sternhagen, Garrett L; Gupta, Sudipta; Zhang, Yueheng; John, Vijay; Schneider, Gerald J; Zhang, Donghui (Journal of the American Chemical Society, 2018)
A series of amphiphilic ionic peptoid block copolymers where the total number (1 or 3) and position of ionic monomers along the polymer chain are precisely controlled have been synthesized by the submonomer method. Upon dissolution in water at pH = 9, the amphiphilic peptoids self-assemble into small spherical micelles having hydrodynamic radius in ∼5–10 nm range and critical micellar concentration (CMC) in the 0.034–0.094 mg/mL range. Small-angle neutron scattering (SANS) analysis of the micellar solutions revealed unprecedented dependence of the micellar structure on the number and position of ionic monomers along the chain. It was found that the micellar aggregation number (N agg) and the micellar radius (R m) both increase as the ionic monomer is positioned progressively away from the junction of the hydrophilic and hydrophobic segments along the polymer chain. By defining an ionic monomer position number (n) as the number of monomers between the junction and the ionic monomer, N agg exhibited a power law dependence on n with an exponent of ∼1/3 and ∼3/10 for the respective singly and triply charged series. By contrast, R m exhibited a weaker dependence on the ionic monomer position by a power law relationship with an exponent of ∼1/10 and ∼1/20 for the respective singly and triply charged series. Furthermore, R m was found to scale with N agg in a power-law relationship with an exponent of 0.32 for the singly charged series, consistent with a weakly charged ionic star-like polymer model in the unscreened regime. This study demonstrated a unique method to precisely tailor the structure of small spherical micelles based on ionic block copolymers by controlling the sequence and position of the ionic monomer.